Acute Cholangitis: An Update in Management Based on Severity Assessment - Robert Christeven; Frandy Frandy; Andersen Andersen (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Acute cholangitis (AC) is a biliary tract emergency which causes significant morbidity and mortality. The direct cause of death in AC is sepsis that leads to irreversible shock and multiple organ failure. The most common predisposition are bile duct stones and previous invasive manipulation of the biliary tree. Biliary infection and biliary obstruction are the two main factors in pathophysiology of AC. Gram-negative bacteria are isolated frequently from bile and blood culture in cholangitis. The most common cause of biliary obstruction is gallstone.The Charcot’s triad which commonly has been used to diagnose AC is severely limited and the clinical presentation of the disease has wide spectrum ranging from mild symptoms to severe life-threatening disease. Thus, the use of the most updated Tokyo Guidelines (TG18) is imperative to diagnose the disease and to assess the severity. The TG18 diagnostic criteria is based on the presence of systemic inflammmation, cholestasis, and evidence on imaging studies of biliary tract. The prompt treatment is tailored according to severity assessed by TG18. Initial treatment includes sufficient fluid replacement, hemodynamic control, electrolyte compensation, intravenous antibiotic administration, and intravenous analgesic administration.  The definitive treatment which related to the pathophysiology of the disease are biliary drainage and antibiotic administration.